2016
DOI: 10.1051/mfreview/2016007
|View full text |Cite
|
Sign up to set email alerts
|

Continuous extrusion and rolling forming of copper strips

Abstract: -Continuous extrusion and rolling technology was proposed as a new strip production technology. It conducts a hot rolling process using waste heat after continuous extrusion. The continuous extrusion and rolling forming was simulated with DEFORM-3D T . Influences of extrusion wheel velocity and rolling reduction on the continuous extrusion and rolling forming were analyzed. It was shown that as extrusion wheel velocity increases, torque of extrusion wheel, chamber force and rolling force, will drop; temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A study of continuous extrusion and the roll forming of copper strips found that after continuous extrusion, a homogeneously distributed and equiaxed grain microstructure can be formed in copper strip billets with an average grain size of about 80 μm. e grains of the copper strips were stretched clearly during rolling and along the rolling direction to form a stable orientation, and after rolling, the grain boundaries are still relatively clear to see [8]. It was reported that the hardness value of the copper layer increased sharply in the first cycle and then remained constant for the next two cycles.…”
Section: Introductionmentioning
confidence: 97%
“…A study of continuous extrusion and the roll forming of copper strips found that after continuous extrusion, a homogeneously distributed and equiaxed grain microstructure can be formed in copper strip billets with an average grain size of about 80 μm. e grains of the copper strips were stretched clearly during rolling and along the rolling direction to form a stable orientation, and after rolling, the grain boundaries are still relatively clear to see [8]. It was reported that the hardness value of the copper layer increased sharply in the first cycle and then remained constant for the next two cycles.…”
Section: Introductionmentioning
confidence: 97%
“…Copper and copper alloys are widely used in industries such as electric, electronic, transportation and machinery manufacturing due to their high electrical and thermal conductivity, good processability, etc [1,2]. Copper and copper alloy sheets and strips are typical copper processed products, and their typical manufacturing methods mainly include Semicontinuous casting and thermo-roll forming, continuous casting and rolling forming, and continuous extrusion and rolling forming, no matter what kind of production method, before getting the required products, will go through the process of 'cold rolling → heat treatment' [3][4][5]. During the cold-rolling process, the grains of copper sheets slip and rotate, forming a cold-rolled texture and generating a large number of point defects, dislocations, and other crystal defects [6,7], so heat treatment is usually required after cold rolling to regulate the microstructure of cold-rolled copper sheets for subsequent forming or to obtain products with the desired properties [8,9].…”
Section: Introductionmentioning
confidence: 99%